Analisis Kepuasan Pengguna Sistem Informasi Manajemen Rumah Sakit Pelni dengan Metode SERVQUAL (Service Quality) - Wafi Hidayat Ahadi; I Ketut Sudaryana (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This study aims to analyze user satisfaction with the Hospital Management Information System (SIMRS) implemented at Pelni Hospital using the SERVQUAL (Service Quality) method. The SERVQUAL method is used to measure Service Quality based on five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The research was conducted by distributing questionnaires to 31 respondents, including patients, medical staff, and administrative staff who actively use SIMRS. The results indicate that, overall, the quality of SIMRS services at Pelni Hospital is categorized as